2017
DOI: 10.4236/gsc.2017.71002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PBr<sub>3</sub> Addition to Polysilane Thin Films on Structures and Photovoltaic Properties

Abstract: Organic thin film solar cells are potential next generation solar cells. Many p-type semiconductors have been used in organic solar cells, but there have been far fewer reports involving n-type organic semiconductors. Developing new n-type organic semiconductors is therefore desirable. Polysilane thin films were spin-coated from solutions containing phosphorus (P), and the effects of P addition on film microstructures and electronic properties as n-type semiconductors were investigated. Microstructures of poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Polysilanes are known as σ-conjugate polymers, and their hole mobility is 10 −4 cm 2 V −1 s −1 [7]. Although the polysilanes could be applied to p-type semiconductors on organic thinfilm solar cells, few studies on polysilane-based solar cells have been reported [8,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Polysilanes are known as σ-conjugate polymers, and their hole mobility is 10 −4 cm 2 V −1 s −1 [7]. Although the polysilanes could be applied to p-type semiconductors on organic thinfilm solar cells, few studies on polysilane-based solar cells have been reported [8,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A common HTL in perovskite solar cells is 2,2 ,7,7 -tetrakis-[N,N-di(p-methoxyphenyl)amine]-9,9 -spirobifluorene (spiro-OMeTAD); however, this HTL is expensive and has poor stability. Alternative low cost and more stable HTLs have been developed [36,37], and other HTL materials, such as polysilanes, have also been utilized with organic photovoltaic devices [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…If even just a little thick film is formed, the resistance value increases and the conversion efficiency decreases [27]. Other polymer materials, including polysilane derivatives, have been applied to organic solar cells [29][30][31]. The polysilanes were also applied as a hole transport layer for perovskite solar cells [32,33], and the photovoltaic performance was improved for a device using decaphenylcyclopentasilane (DPPS).…”
Section: Introductionmentioning
confidence: 99%